Optimal Management of Genetic Diversity in Subdivided Populations - López-Cortegano, Eugenio; Pouso, Ramón; Labrador, Adriana; Pérez-Figueroa, Andrés; Fernández, Jesús; Caballero, Armando (Frontiers in Genetics, 2019)
One of the main objectives of conservation programs is the maintenance of genetic diversity, as this provides the adaptive potential of populations to face new environmental challenges. Genetic diversity is generally assessed by means of neutral molecular markers, and it is usually quantified by the expected heterozygosity under Hardy-Weinberg equilibrium and the number of alleles per locus, or allelic diversity. These two measures of genetic diversity are complementary because, whereas the former is directly related to genetic variance for quantitative traits and, therefore, to the short-term response to selection and adaptation, the latter is more sensitive to population bottlenecks and relates more strongly to the long-term capacity of adaptation of populations. In the context of structured populations undergoing conservation programs, it is important to decide the optimum management strategy in order to preserve as much genetic diversity as possible, while avoiding inbreeding. Here we examine, through computer simulations, the consequences of choosing a conservation strategy based on maximizing either heterozygosity or allelic diversity of SNP haplotypes in a subdivided population. Our results suggest that maximization of allelic diversity can be more efficient in maintaining the genetic diversity of subdivided populations than maximization of expected heterozygosity, because the former maintains a larger number of alleles while making a better control of inbreeding. Thus, maximization of allelic diversity should be a recommended strategy in conservation programs for structured populations.